2010
DOI: 10.1093/ntr/ntq193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Tobacco Use Among a Sample of MSM in Shanghai, China

Abstract: Introduction: Men who have sex with men (MSM) have higher smoking rates than the general population in the United States, but less is known about smoking among MSM in developing countries. Thus, we examined the prevalence and correlates of smoking among MSM in China. Methods:We conducted a cross-sectional study of 404 MSM in Shanghai, China (half of whom were male sex workers), recruited through respondent-driven sampling. Assessments included sociodemographics; tobacco, alcohol, and drug use; the Center for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
1
35
2
Order By: Relevance
“…Several studies found associations between demographic correlates of smoking that are similar to characteristics identified in the general population, including younger age30 64 65 and lower educational attainment 8 14 21 31 65–67. Other common correlates with smoking were alcohol use14 31 65 68 and depression/depressive symptoms 30 65 69.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Several studies found associations between demographic correlates of smoking that are similar to characteristics identified in the general population, including younger age30 64 65 and lower educational attainment 8 14 21 31 65–67. Other common correlates with smoking were alcohol use14 31 65 68 and depression/depressive symptoms 30 65 69.…”
Section: Resultsmentioning
confidence: 75%
“…Other common correlates with smoking were alcohol use14 31 65 68 and depression/depressive symptoms 30 65 69. One small study using a convenience sample found no associations between income and age with smoking 67…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the individual-level constructs of depression, sexual attitudes, and gay identity, were not predictive of lifetime drug use. Some previous research has shown these factors to be pertinent to drug, alcohol and tobacco use behaviors among Chinese MSM in Shanghai (Berg et al, 2011;Nehl et al, 2011;Wong et al, 2010;Yu et al, 2013). However, the most recent study among Chinese MSM and MBs also did not find psychosocial associations with drug use .…”
Section: Discussionmentioning
confidence: 94%
“…Men who have sex with men (MSM) are at high risk for smoking (Greenwood et al, 2005;Lampinen, Bonner, Rusch, & Hogg, 2006;McKirnan, Tolou-Shams, Turner, Dyslin, & Hope, 2006;Tang et al, 2004), but limited research has examined smoking among MSM in developing countries. One study of MSM in Shanghai, China documented a 66% smoking prevalence (Berg et al, 2011). Reasons for these elevated risks might include higher stress or depression, discrimination, and lack of social support (Choi et al, 2003;Liu & Choi, 2006;Pilcher, 2003).…”
Section: Introductionmentioning
confidence: 99%